Voltage- and temperature-dependent rare-earth dopant contribution to the interfacial magnetic anisotropy. (8th July 2020) - Leon, Alejandro O; Bauer, Gerrit E W
Abstract: The control of magnetic materials and devices by voltages without electric currents holds the promise of power-saving nano-scale devices. Here we study the temperature-dependent voltage control of the magnetic anisotropy caused by rare-earth (RE) local moments at an interface between a magnetic metal and a non-magnetic insulator, such as Co|(RE)|MgO. Based on a Stevens operator representation of crystal and applied field effects, we find large dominantly quadrupolar intrinsic and field-induced interface anisotropies at room temperature. We suggest improved functionalities of transition metal tunnel junctions by dusting their interfaces with rare earths.